Analysis of the Effectiveness of the Implementation of the SEJAK-GO Application (Automatic Free Health Insurance Enrollment System) in the Registration of Regional Government PBPU Participants for BPJS Health at Hospitals - Rieny Widyanty; Misnaniarti Misnaniarti; Rostika Flora (Journal La Medihealtico, 2026)
Digital transformation in healthcare services has become one of the key strategies for improving the effectiveness of health administration services, particularly for BPJS Health participants. One of the digital innovations utilized in health administration services is the SEJAK-GO application (Automatic Free Health Insurance Entry System), which is employed in the registration process of Regional Government PBPU BPJS Health participants at hospitals. This study aims to analyze the effectiveness of the SEJAK-GO application implementation in improving the quality of health administration services. The research method employed is a Systematic Literature Review (SLR), analyzing various scientific journals related to the digitalization of BPJS services, Mobile JKN, online registration systems, and Hospital Management Information Systems (SIMRS) within the period of 2021–2026. The review findings indicate that the implementation of digitally-based healthcare service systems is capable of improving administrative service effectiveness through accelerated patient registration processes, reduced service queues, integration of healthcare service data, and increased work efficiency of hospital administrative staff. The implementation of the SEJAK-GO application is interconnected with various BPJS digital service systems as it functions as an automatic data entry system for health insurance participants. Nevertheless, the effectiveness of digital system implementation is still influenced by technology infrastructure readiness, internet network quality, health information system integration, and human resource competency. Accordingly, the SEJAK-GO application has the potential to become a digital innovation that supports the improvement of BPJS PBPU Pemda administrative service quality at hospitals in a more effective, efficient, and integrated manner.